PEMETAAN PARA PIHAK DALAM PEMULIHAN KHDTK SAMBOJA - Subekti Rahayu; Sambas Basuni; Agus Priyono Kartono; Agus Hikmat (Jurnal Analisis Kebijakan Kehutanan, 2018)
Forest and land rehabilitation at kawasan hutan dengan tujuan khusus (KHDTK) Samboja, East Kalimantan had been started in 1988. Many stakeholders were involved in the activities through different mechanisms. However, this program was still far beyond expectation as the success of the rehabilitation program was limited only at the research site of the KHDTK Samboja. Information on potential stakeholders and their roles in the program is needed to formulate a better plan that will be used as a guidance to achieve an effective, efficient and sustainable restoration program in the future. An interview with key informants using snowball sampling method was carried out in BPTKSDA Samboja to identify potential stakeholders that will be involved in the future restoration program, including their interests and possible impacts on the program. The result showed that there was 11 stakeholders that could be engaged in the future Samboja Research Forest Restoration Program; BPTKSDA Samboja, UPTD Tahura Bukit Soeharto, Foresty Officer, Mulawarman University and FOERDIA as key players; Dipterocarp Research Centre and Indonesia Institute of Science as context setter; land manager and forestry industrial companies as subject; non land manager and mining companies as crowd.